Panitumumab: leading to better overall survival in metastatic colorectal cancer?. (April 2014) - Sebio, Ana; Stintzing, Sebastian; Stremitzer, Stefan; Zhang, Wu; Lenz, Heinz-Josef
<x xml:space="preserve">Abstract</x> Introduction: Survival of metastatic colorectal cancer (mCRC) patients has improved greatly over the past few years, essentially due to the appearance of new biological therapies. Among these new therapies, monoclonal antibodies targeting the EGFR are the leading contributors to the so-called personalized medicine. Biomarkers within the EGFR pathway, such as K-Ras mutation, have proved to help better select the patients benefiting from these treatments. Areas covered: <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Panitumumab&logicalOpe1=OR&field2=articletitle&text2=Panitumumab&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Panitumumab is a fully human monoclonal antibody that targets the EGFR and is currently approved in combination with chemotherapy or in monotherapy for the treatment of mCRC patients. Following a description of the pharmacological and tolerability data, this review focuses on the clinical activity of panitumumab through the description of clinical trials and biomarker research. Expert opinion: Recent biomarker research with expanded Ras testing has led to an improvement in overall survival for all Ras wild-type patients treated with panitumumab. Furthermore, the thorough evaluation of markers within the EGFR pathway could potentially prevent detrimental effects for patients treated with panitumumab and avoid unnecessary toxicity and costs.